Alternative option for limb reperfusion cannula placement for percutaneous femoral veno-arterial ECMO. (July 2022) - Göbölös, Laszlo; Hogan, Maurice; Kakar, Vivek; Raposo, Nuno; Sänger, Stefan; Bhatnagar, Gopal; Park, Woosup Michael
Veno-arterial extracorporeal membrane oxygenation (VA ECMO) is an established last line support for severe, acute cardiorespiratory failure. In the case of VA ECMO, peripheral cannulation via the femoral vessels is often advantageous when compared with the alternative central cannulation, and is associated with better clinical outcomes. One of the specific potential complications of peripheral femoral arterial cannulation for ECMO, however, is ipsilateral distal lower limb ischemia; a consideration especially when cannulating the vessel directly, as distal limb perfusion is invariably compromised by an occlusive effect of the arterial cannula within the femoral artery. The gold standard technique for lower limb reperfusion is a separate size 6–7 Fr cannula inserted proximally into the femoral artery, just below the insertion point of the ECMO return cannula, and connected directly to the ECMO circuit so that the blood flow is also directed distally to perfuse the entire limb. This functions well whether the ECMO cannula has been placed percutaneously or by surgical cut-down. Although proximal femoral arterial placement of the reperfusion cannula is the established and preferred technique, there are many technical challenges which may preclude its placement. Local haematoma or bleeding post ECMO insertion, peripheral vascular disease, constricted vasculature in severely shocked patients, or patient obesity are all common reasons why placement of the proximal reperfusion cannula may be difficult, or impossible. In such instances, our retrograde perfusion technique may maintain limb perfusion and may even be limb saving for patients on VA ECMO support.